Gastric peroral endoscopic pyloromyotomy for decompensated gastroparesis: comprehensive motility analysis in relation to treatment outcomes - Conchillo, José M.; Straathof, Jan Willem A.; Mujagic, Zlatan; Brouns, Jenny H.; Bouvy, Nicole D.; Keszthelyi, Daniel; Masclee, Ad A.M. (Endoscopy International Open, 2021)
Background and study aims There are no reliable data to predict which patients with gastroparesis (GP) would benefit the most from gastric peroral endoscopic pyloromyotomy (G-POEM). The aim of the present study was to assess whether antro-duodenal motility patterns and pyloric distensibility can predict the outcome of G-POEM in patients with decompensated GP.Patients and methods In an open-label study, patients with GP and refractory symptoms were eligible for treatment with G-POEM if treatment attempts according to a standardized stepwise protocol had failed. Baseline assessment included Gastroparesis Cardinal Symptom Index (GCSI), C13-octanoic gastric emptying breath test and high-resolution antro-duodenal manometry. Pyloric distensibility using EndoFlip measurements was assessed at baseline and 3 months after the procedure. Explorative analyses were performed on potential predictors of response using logistic regression analyses.Results Twenty-four patients with decompensated GP underwent G-POEM. At baseline, 78.3 % and 61.9 % of patients showed antral hypomotility and neuropathic motor patterns, respectively. The technical success rate was 100 % (24/24). Mean GCSI improved significantly at 3, 6, and 12 months after G-POEM (P = 0.01). Median distensibility index (DI) improved significantly as compared with baseline (7.5 [6.9;11.7] vs. 5.3[3.1;8.1], P = 0.004). A significant correlation was found between clinical response at 6 months and pyloric DI improvement (P = 0.003). No potential predictors of clinical response after G-POEM could be identified in an explorative analysis.Conclusions G-POEM improved pyloric distensibility patterns in patients with decompensated GP. Clinical response at 6 months after G-POEM was associated with pyloric distensibility improvement. However, no potential predictors of response could be identified from either antro-duodenal motility patterns or pyloric distensibility.